Evaluasi Sistem Distribusi dan Tingkat Bunga Beban Gaduhan Ternak Sapi Bibit Provinsi Jambi - Novra, Ardi; Pramushinto, Bagus (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2011)
The research objective to evaluating of the heifer distribution system which’s can be using as a base of the capacity building program of the farmer institution empowerment. The research survey doing 8 (eights) month which’s unit analysis is the livestock farmer households who’s receive the meat cow on the breeding program. Data collected by multi-stage cluster random sampling at the three regencies which’s representative of the three regions of Jambi Province were west, middle and east. Data analyzed using the compound interest and structural equation model with threes equation behavior divide 3 endogenous and 6 exogenous variable. The result of the research can be indicated that the interest rate of the 1 : 2 system was 22,65% and this rate more than higher from Grati system (6,60%), 1 : 1 system (4,39%) and so commercial credit investment. The evaluation of the distribution system show that the long time to first restore cattle are not different among the system rotate (average > 30 months), the level of restored is lowest and predicted will be more length than contract period (60 months). This level of restored significantly influenced by the share cropping system, the first of restored period, and the running of shared cropping period. The interest rate of which’s must be pay by households different significantly among the share cropping system and will be significantly effected by the time period of the restored. Based on the result and discussion will be conclude that not only unfair among the share cropping system but on the same system too. Nothing incentive as a reward of the fast of restored will be decreasing the household livestock motivation to effort to acceleration of their heifer productivities.